Functional feeding groups of aquatic insect families in Latin America: a critical analysis and review of existing literature - Ramírez, Alonso (Universidad de Costa Rica, 2014)
Aquatic macroinvertebrates are involved in numerous processes within aquatic ecosystems. They often have important effects on ecosystem processes such as primary production (via grazing), detritus breakdown, and nutrient mineralization and downstream spiraling. The functional feeding groups (FFG) classification was developed as a tool to facilitate the incorporation of macroinvertebrates in studies of aquatic ecosystems. This classification has the advantage of combining morphological characteristics (e.g., mouth part specialization) and behavioral mechanisms (e.g., way of feeding) used by macroinvertebrates when consuming resources. Although recent efforts have greatly advanced our ability to identify aquatic macroinvertebrates, there is limited information on FFG assignment. Furthermore, there has been some variation in the use of the FFG classification, in part due to an emphasis on using gut content analysis to assign FFG, which is more appropriate for assigning trophic guilds. Thus, the main goals of this study are to (1) provide an overview of the value of using the FFG classification, (2) make an initial attempt to summarize available information on FFG for aquatic insects in Latin America, and (3) provide general guidelines on how to assign organisms to their FFGs. FFGs are intended to reflect the potential effects of organisms in their ecosystems and the way they consume resources. Groups include scrapers that consume resources that grow attached to the substrate by removing them with their mouth parts; shredders that cut or chew pieces of living or dead plant material, including all plant parts like leaves and wood; collectors-gatherers that use modified mouth parts to sieve or collect small particles (<1mm) accumulated on the stream bottom; filterers that have special adaptations to remove particles directly from the water column; and predators that consume other organisms using different strategies to capture them. In addition, we provide details on piercers that feed on vascular plants by cutting or piercing the tissue using sharp or chewing mouth parts and consume plant liquids. We also provide a list of families of aquatic insects in Latin America, with an initial assignment to FFGs. We recommended caution when assigning FFGs based on gut contents, as it can provide misleading information. Overall, FFG is a very useful tool to understand the role of aquatic macroinvertebrates in stream ecosystems and comparisons among studies will benefit from consistency in their use. Rev. Biol. Trop. 62 (Suppl. 2): 155-167. Epub 2014 April 01.